Innovative invention skills and individual competency model for vocational education - Lai, Chee Sern; Sulaiman, Nor Lisa; Mohamad, Mimi Mohaffyza; Mohd Salleh, Kahirol (IJIET, 2017)
Invention is a process of developing creative minds, innovative and inventive in preparing the workforce informed, and competent in facing the challenges of rapid technological development today. Knowledge and individual competency are needed to produce a new design of a product. Knowledge and skills are the components related to invention process that could be identified easily. Therefore, this study aimed to determine the level of student’s knowledge and preferences in invention process, student’s skills in selecting the process knowledge, and to identify the relationship between the student’s knowledge and the preferences process that they chose. 528 students from vocational colleges were involved in this study. The set of questionnaires based on Renwick model and iceberg competency model was used to measure the variables needed. The results showed the level of student’s knowledge in invention process was high and the students also preferred the idea of development when they chose the invention process. This study also concluded that there was a significant relationship between knowledge and student’s preferences in invention process. In conclusion, the application of skills and knowledge in invention process will be applied in students’ competency and it is capable of developing new ideas to create innovative and creative products.